TAXATION, FOREIGN DIRECT INVESTMENT, AND HUMAN CAPITAL DEVELOPMENT: EVIDENCE FROM PAKISTAN (Contemporary Journal of Social Science Review, 2025)
This study examines the effects of taxation, foreign direct investment, interest rate, and other variables, such as the youth unemployment rate and primary enrolment, on the human capital of Pakistan between 1994 and 2024, with implications for the broader developing world. The time-series econometric analysis reveals a substantial negative correlation between the tax-to-gross domestic product ratio and human capital. This relationship is explained by the regressive nature of Pakistan’s tax system and the low proportion of government spending allocated to education and health. In contrast, inflows of foreign direct investment exhibit a positive and significant effect on human capital, primarily by generating employment, facilitating the transfer of technology, and fostering the development of skills. However, foreign direct investment in Pakistan remains limited and is largely concentrated in sectors with low spillover potential. A comparative analysis with countries such as Bangladesh, India, and Sri Lanka reveals inefficiencies in Pakistan’s outcomes, despite similar or superior fiscal capacity, highlighting governance quality and the effectiveness of public spending as key constraints. The evidence demonstrates that taxation alone is insufficient to enhance human capital without effective allocation of resources, and that even relatively small amounts of foreign direct investment can produce tangible improvements when directed towards appropriate sectors. The policy implications include the need for gradual reforms to the taxation system, increased and better-targeted government expenditure, and strategies to attract foreign direct investment into industries that are intensive in human capital development. The study emphasises the necessity of a coherent national strategy to transform Pakistan’s demographic potential into sustained economic growth through substantial investment in human capital.